SUBTITUSI IMPOR DAGING MELALUI SISTEM KONTRAK BAGI HASIL TERNAK (Proceeding Fakultas Ekonomi, 2013)
This research is aimed at flnding the signilicani characteristics of livestock management which indicate the varieties of the profit-shared coiliract of livestock lihinagemeni. II is cxpccied that by eiiidcrslandiiig each of ihosc characteristics, Iwople may oplimilc the results of the imlliagenwnt system ot livestock. 11w study relates to cattle faitciiing. breeding cattle. buffaloes and goats. The research which was conducted in Boyolali. Central Java in 2(WW) insolved 711 respondents. The data were piocessesl by Principal Component Analysis (Pt’A. and the main lactors that showed the significant varieties of livestock manage.iwnt were caictilated by using l)iscriminant Analysis. The results of the analyses indicate time major coiliponelits hich were signilicant in the contract system, i.e.: (I Factor I: the aspects of agent’s net rcvcnuc and the principal shame. (21 Factor 2: the aspects of rulio ol contract revenue. (3) Factor 3: the aspects of agent’s share. (4) Factor 4: the aspects of transaction costs. (5) Factor 5: the aspects ol transport costs and time allocation for eluintenanee. (6) Factom 6: the aspects of agents gross revenue, (7) Factor 7: the aspects of family sizc. (11) Factor : tlw aspects of experience in maintaining livestock, (9) Factor Q: the aspects of principal income. The results may recommend that mnisnaging livestock with profit-shared contract should he more effective and efficient hen people consider the characteristics of agents in managing livestock. It is comparatively an advantage that there are so many livestock farmers who acted as agents in Indonesia. iTherefore, they are an incredible asset to produce meat in an attempt to substitute the imported meat. Kcword.s: contract system. livestock management. principal, agent. substitution of imported meat